Resistance Against Zionism on Scarf Store Instagram Accounts: A Semiotic Analysis - Nadillah, Ana Luciani Kholda Farah; Nainggolan, Erni Susianti (CV. Tripe Konsultan, 2026)
This study investigates how resistance to Zionist actions in Palestine is represented through visual and textual signs on Instagram accounts that sell Palestinian headscarves. The problem addressed in this study is how signs embedded in headscarf motifs and accompanying captions function as symbols of resistance and solidarity in digital spaces. The objective of this study is to identify and interpret the meanings of these signs as expressions of political resistance. The study subjects consist of posts from selected Instagram accounts that market Palestinian headscarves, chosen through purposive sampling based on their explicit association with Palestinian solidarity content. The data comprise visual elements of headscarf motifs as well as captions and hashtags used in the posts. This study employed a descriptive qualitative approach. Data were collected through documentation of Instagram posts and analyzed using a semiotic approach supported by resistance theory to interpret representational meanings. The analysis focuses on the classification of signs and their interpretative meanings within the context of resistance. The findings reveal a total of 74 signs found in the headscarf motifs that represent resistance-related issues, including the keffiyeh symbol, mosque imagery, and the Palestinian flag. These signs convey meanings of collective identity, solidarity, cultural preservation, and opposition to oppression. In conclusion, Instagram serves not only as a commercial platform but also as a medium for symbolic resistance, where headscarf motifs function as visual tools to communicate political messages and support for the Palestinian struggle. This study contributes to understanding digital activism through semiotic representation and highlights the role of fashion-related media in contemporary resistance movements.